Haematologic profile of haemoglobin constant spring and its co-inheritance with alpha and beta thalassaemia among form four students in Negeri Sembilan - Nahanthiran, Subithira; Nik Mustapha, Nik Hafidzah; Chellappah Thambiah, Subashini; Osman, Malina; Idris, Faridah; Md Noor, Sabariah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: In Malaysia, the commonest non-deletional alpha (α) thalassaemia is Haemoglobin Constant Spring (Hb CS) which occurs due to a mutation at the termination codon of α2 globin gene (TAA>CAA). Presence of an abnormal peak at Zone 2 on CE or presence of a small peak at c-window on HPLC can be suggestive of Hb CS. The objective of this study was to determine the proportion of form four students diagnosed with Hb CS and to study the haematologic profile of Hb CS and its co-inheritance with α or beta (β) thalassaemia. Methods: This was a cross-sectional study carried out at Hospital Tuanku Ja’afar Seremban (HTJS), involving 15-16 year old secondary school students screened for thalassaemia. The proportion of Hb CS and Hb CS with α or β thalassaemia co-inheri- tance was calculated and the correlation between the full blood count (FBC) parameters with CE and HPLC results were determined. Results: A total of 3121 students were diagnosed to have thalassaemia and the proportion of Hb CS was 3.24%. Hb CS with α thalassaemia co-inheritance had significantly lower mean corpuscular volume (MCV) compared to Hb CS without co-inheritance and Hb CS with β thalassaemia co-inheritance, t(2)=4.16, p=0.02. This study also has shown that the mean corpuscular haemoglobin (MCH) was significantly lower in Hb CS with α thalas- saemia co-inheritance t(2)=9.89, p<0.01. Conclusion: The combination of both, FBC parameters and Hb analysis can be used in screening and in making a presumed diagnosis of Hb CS or co-inheritance with alpha thalassaemia.